Pulling the Trigger: Recommendations for Surgical Care of the Pediatric Trigger Thumb. Issue 6 (July 2020) - Dittmer, Alison J.; Grothaus, Olivia; Muchow, Ryan; Riley, Scott
Abstract : Background: Despite being a common pediatric hand condition, there are few clear guidelines regarding the optimal management of pediatric trigger thumb. Our primary aim was to help guide surgical management of this disorder by establishing a treatment algorithm on the basis of our institution's experience. Methods: This is an institutional review board-approved retrospective study of all patients with idiopathic trigger thumbs from 2005 to 2015 at a single institution. Demographics and treatment course were recorded for all patients including duration of follow-up, observation, surgical intervention, and complications. All children were classified according to the Sugimoto classification. Results: A total of 149 patients with 193 thumbs met inclusion and exclusion criteria. 16.5% of patients had stage II thumbs, 10.3% of patients with stage III, and 73% of patients with stage IV thumbs. Of all patients with stage IV thumbs, 3.5% were locked in extension for an overall incidence of 2.6%. In total, 46% of patients failed observation and underwent surgical treatment. Only 14% of stage IV trigger thumbs resolved when observed, compared with 53% of stage II and 25% of stage III trigger thumbs. Stage IV thumbs were 4.6 times more likely to fail conservative treatment and go on to surgery than stage II or III thumbs (odds ratio, 4.6; P =0.006). Thirty-two percent of patients underwent surgery without an observation period. Older children with bilateral stage 3 thumbs were the most likely to go straight to the odds ratio instead of being observed ( P =0.002, r 2 =0.17). Of the total amount of patients who underwent surgery (116), there were 4 complications for a rate of 3.4% with a recurrence rate of 1.7%. Conclusions: On the basis of the data in this study, the authors would recommend that stage IV thumbs undergo surgery without an observational period. Second, stage II and stage III thumbs can be safely observed for at least 1 year before surgery. Finally, our study concurs with the literature that surgery can be successful with low rates of complications and recurrence. Level of Evidence: Level IV.